Corkscrew motion of Trypanosoma brucei is driven by helical beating of the flagellum and facilitated by its bent shape - Sizhe Cheng; Devadyouti Das; Mykhaylo Barchuk; Raveen Armstrong; Michele M. Klingbeil; Becca Thomases; Shuang Zhou (Proceedings of the National Academy of Sciences, 2026)
In the pathogenic parasite Trypanosoma brucei , a laterally attached flagellum drives rapid deformation of the complex cell body, producing puzzling dynamics. High-speed defocusing imaging reveals that surface points trace flower-like patterns in transverse planes. The petals arise from clockwise flagellar beating, which generates a right-handed helical wave propagating from the anterior tip along the body, advancing the cell like a twisted corkscrew. The central lobes result from slower counterclockwise body rotation required to balance the active torque. The bent cell shape underneath the flagellum superimposes these two chiral motions at different radial distances, producing the observed patterns. Three-dimensional hydrodynamic simulations using the method of regularized Stokeslets reproduce these dynamics and show that bent cell shape enhances swimming, suggesting an adaptive advantage of T. brucei ’s morphology.